Pengaruh Kemudahan Penggunaan, Persepsi Risiko, Dan Kepercayaan Nasabah Terhadap Loyalitas Pengguna Brimo (Studi Pada Mahasiswa Universitas Islam Malang) - Windiana, Chelsea; Mustapita, Arini Fitria; Dianawati, Eris (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to identify and assess how ease of use (X1), risk perception (X2), and customer trust (X3) affect BRImo user loyalty (Y). This study adopts a quantitative research design and uses a probability sampling technique specifically, stratified random sampling with a total of 60 respondents. These respondents are students of the 2021 intake at the Islamic University of Malang. The data were analyzed using various tests, including validity, reliability, normality, multicollinearity, and heteroscedasticity tests, along with multiple linear regression analysis. In addition, the F test (for simultaneous effects), t test (for individual effects), and coefficient of determination tests were conducted using SPSS 30. The findings indicate that ease of use and customer trust have a significant positive effect on loyalty, both individually and collectively, while risk perception has a significant partial negative impact on loyalty. Keywords: Ease Of Use, Risk Perception, Customer Trust, User Loyalty